Development Of Ultrasonic Cautery System - Yap, Kah Weng (Universiti Sains Malaysia, 2021)
The use of piezoelectric element as the primary ultrasonic transducer is prevalent in ultrasonic cautery system. Proper method to characterize an ultrasonic scalpel has become an important design process. In this study, an ultrasonic scalpel prototype was characterized using both finite element modelling and experimental procedures. FEM simulation software, Abaqus was utilized to investigate preloading effects, proper longitudinal mode shape, resonant frequency, and mechanical response due to harmonic excitation. Experimental modal and harmonic analyses were used for experimental validation. The simulated results were in accordance to the theoretical calculation for the preloading effects, where sufficient compressive stress of 27 MPa was imposed onto the piezoceramic rings and an internal stress developed within the bolt approached 190 MPa. Modal analysis detected a resonant frequency at 47740 Hz with a dominant longitudinal mode shape. For harmonic analysis, simulated result suggested 76.85 microns of mechanical displacement amplitude while experimental procedure measured 54 microns. The results concluded that the ultrasonic scalpel was successfully characterized.